Klucze - Kuncewiczowa, Maria Szczepanska, 1897- (Lublin : Wydawnictwo Lubelskie, 1990)
More autobiographical material by the well-known Polish author.
Keywords: Kuncewiczowa, Maria Szczepanska, -- 1897-; World War, 1939-1945 -- Personal narratives, Polish; Authors, Polish -- 20th century -- Biography